Hot isostatically pressed Y2Ti2O7 and Gd2Ti2O7 pyrochlore glass-ceramics as potential waste forms for actinide immobilization. Issue 4 (April 2019) - Wei, Tao; Zhang, Yingjie; Kong, Linggen; Kim, Young Jip; Xu, Alan; Karatchevtseva, Inna; Scales, Nicholas; Gregg, Daniel J.
Graphical abstract: Both Y2 Ti2 O7 and Gd2 Ti2 O7 pyrochlore glass-ceramics have been prepared with a typical oxide route and consolidated via hot isostatic pressing, and characterized as potential waste forms for the immobilization of actinide-rich radioactive wastes. Abstract: Both Y2 Ti2 O7 and Gd2 Ti2 O7 pyrochlore glass-ceramics (GCs) have been prepared with an oxide route and consolidated via hot isostatic pressing (HIPing) as waste forms for actinide immobilization. The crystallization of Y2 Ti2 O7 /Gd2 Ti2 O7 pyrochlore as the major actinide host phase in the residue glass has been confirmed with XRD, SEM-EDS and Raman spectroscopy. The static leaching tests confirmed that both GCs are chemically durable with normalized Y/Gd and Ti leach rates ∼10 −4 –10 -5 g m -2 d -1 after 28 days. In addition, the interactions between the 316L stainless steel (SS) HIP-can and the GCs have been investigated. Interactions occur at the interface with a layer of mixed Cr/Ti oxide and CrTi2 O5 crystals observed for the Y2 Ti2 O7 GC and a layer (∼10 μm) of Cr2 O3 observed for the Gd2 Ti2 O7 GC as the reaction fronts from the SS cans. Furthermore, a layer (∼10 μm) of Gd-(Si/Ti)-oxide phase formed on the GC side of the interface.